Engineering Solutions for the Next Millennium. 1999 IEEE Canadian Conference on Electrical and Computer Engineering (Cat. No.99
DOI: 10.1109/ccece.1999.804957
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure release and test techniques for high-temperature micro hotplate

Abstract: We report several practical issues in the fabrication and high-temperature operation of micro suspended heating structures compatible with standard CMOS technology. Suspended microstructures are fabricated in a standard CMOS process and are released by post-process silicon etching. TMAH at 25wt% with 15~01% of IPA is found to greatly increase yield by reducing mechanical disturbances during etching. Electro-thermal properties of the polysilicon are investigated during high-temperature operation. Significant th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…The decrease of the resistance could be caused by the recrystallisation of polysilicon at high temperatures, as it has been described in the literature [21,25]. A drift of the electrical power after a few cycles above 40 mW/beam was observed (Fig.…”
Section: Electrical Propertiesmentioning
confidence: 62%
“…The decrease of the resistance could be caused by the recrystallisation of polysilicon at high temperatures, as it has been described in the literature [21,25]. A drift of the electrical power after a few cycles above 40 mW/beam was observed (Fig.…”
Section: Electrical Propertiesmentioning
confidence: 62%
“…Under these conditions of high-temperature operation, the polysilicon heater material is not stable enough 9 to be used simultaneously as both a heater and a temperature sensor. Accordingly, we used an additional temperature sensor, and also a polysilicon resistor, located on one of the supporting arms closer to the substrate at a lower temperature, which can be used for temperature control.…”
Section: Device Design Characteristics and Fabricationmentioning
confidence: 99%
“…It was found that at temperatures below a certain threshold, estimated to be between 400 and 500°C, poly-1 was stable enough. 9 Since it is expected that the heater resistive load will vary during the operation, a power supply integrated circuit delivering constant power is used in order to keep the temperature of the microhotplate constant. The power supply, based on an analog multiplier with feedback stages, delivers constant power within Ϯ1% when the microheater resistance changes within Ϯ50%, up to 40 mW on heater loads in the range 1-10 k⍀.…”
Section: Device Design Characteristics and Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…The most obvious material that was first used as heater was polysilicon (polySi) [1,15,16]. Poly-Si is useful up to 550 • C, above which its resistivity becomes unstable [17,18]. Lately, heaters based on monocrystalline silicon were developed for CMOS hotplates but these MOSFET type heaters still suffer of a lack of stability at high temperature [19,20].…”
Section: Introductionmentioning
confidence: 99%